To live with(out) violence a second look 2--excerpts : final report violence against women Zenica, Bosnia-Herzegovina - Peele, Holly; Andric-Ruzicic, Duska (Medica Infoteka, 1999)
Excerpts from the original book written in the Bosnian language by Medica professionals working in the Women's Therapy Center. These professionals relate their experiences in working with these women survivors of violence